HUMAN RESOURCE MANAGEMENT STRATEGY IN IMPROVING BAZNAS PERFORMANCE IN DIGITAL ERA - YONGKI GUNAWAN; AMIMAH OKTARINA; KHAIRIAH ELWARDAH; ESTI ALFIAH (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The growth of zakat in Indonesia is very rapid, this is because the majority of Indonesia's population is Muslim so the development of Islamic social financial institutions has an important role for the community. On the other hand, zakat has a potential contribution in reducing poverty. The purpose of this research is to analyze the strategy of developing human resources in improving the performance of BAZNAS in the digital age. Accuracy in placing human resources and the ability to respond responsively to the progress of the digital age are indicators that are measured to determine the extent of BAZNAS capabilities in the digital age. The research method used is descriptive qualitative by obtaining factual data to be used as an analytical tool in this study. The expected outcome is a strategy to develop human resources that are oriented to improving the competence of BAZNAS human resources in the digital world and also have sharia values characteristics ranging from recruitment placement to evaluating human resource performance.